On the Solution of a Linear Fuzzy Cauchy Problem with Constant Coefficients - Komleva, Tatyana (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
In this report we consider a linear fuzzy Cauchy problem with constant coefficients and present an analytical formula for its solution. У цій роботі розглядається лінійна нечітка задача Коші з постійними коефіцієнтами та надається аналітична формула її розв'язку.